2018
DOI: 10.1080/10773525.2018.1507187
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of musculoskeletal disorders among Indian railway sahayaks

Abstract: Railway sahayak or also known as coolie is one of the oldest occupations in India. This occupational group is continuously subjected to various musculoskeletal problems due to repetitive load exertion in unnatural postures. The present research aims to examine the prevalence of musculoskeletal disorders (MSDs) among Indian railway sahayaks. A cross-sectional study has been conducted on a sample of 51 male sahayaks. With a modified Nordic questionnaire, data were collected on their demographics, work, and muscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…From this study, it was also revealed that Indian railway track maintainers perform different types of heavy activities in an awkward posture, with repetition of work by which they suffer from WRI and MSP in different parts of their body. Although there is no other similar study reported in the literature with which to compare the results, these findings are consistent with previous epidemiological reports of MSP among relatively similar occupations involving Indian railway porters (Khan and Singh, 2018); construction industry (Lette et al, 2018); meat processing industry (Tappin et al, 2008); and brickfield workers (Das, 2015(Das, , 2019a. This high prevalence suggests that it would be worthwhile to examine whether track maintainance tasks are an important risk factor contributing to the development of MSDs among track maintainers.…”
Section: Discussionsupporting
confidence: 89%
“…From this study, it was also revealed that Indian railway track maintainers perform different types of heavy activities in an awkward posture, with repetition of work by which they suffer from WRI and MSP in different parts of their body. Although there is no other similar study reported in the literature with which to compare the results, these findings are consistent with previous epidemiological reports of MSP among relatively similar occupations involving Indian railway porters (Khan and Singh, 2018); construction industry (Lette et al, 2018); meat processing industry (Tappin et al, 2008); and brickfield workers (Das, 2015(Das, , 2019a. This high prevalence suggests that it would be worthwhile to examine whether track maintainance tasks are an important risk factor contributing to the development of MSDs among track maintainers.…”
Section: Discussionsupporting
confidence: 89%
“…High intensity workloads on the spine experienced by railway workers contribute to formation and acceleration of degeneration processes in the lumbar segments [14]. This leads to the formation of LDH, deformities and segmental instability associated with persistent radicular neurological manifestations requiring surgical treatment [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that heavy physical work may contribute to the development of degenerative changes in the lumbar spine segments [13]. This leads to acceleration of degenerative disk disease with the development of clinical compression symptoms, which reduces the preoperative workload of Railway workers [14]. The ability to maintain tolerance to intense physical activity with the restoration of previous professional activities is important for this category of patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…This prevalence is also comparable to the prevalence of MSDs reported among manual harvesting farmers of Rajasthan (77.9%) [ 21 ] and construction workers (77%) in Andhra Pradesh [ 22 ]. Surprisingly, this burden is higher than the prevalence of MSDs in railway sahayaks/coolies (65%) [ 23 ] and industrial workers (59.4%) [ 24 ], and the general population (25.9%) in India [ 25 ]. This high burden of MSDs among HCPs compared to heavy workers and general people raises concerns regarding the ergonomics of the work environments in Indian healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%